Преобразуйте произведение в сумму и объясните

0 рейтинг

Преобразуйте произведение в сумму и объясните


в разделе Алгебра
Всего ответов: 1
0 рейтинг
Правильный ответ

пользуемся формулой:

cosx*cosy=\frac{1}{2}(cos(x-y)+cos(x+y))\\ \\ cos\frac{\pi}{8} *cos\frac{\pi}{5}=\frac{1}{2}(cos(\frac{\pi}{8}-\frac{\pi}{5})+cos(\frac{\pi}{8}+\frac{\pi}{5}))=\frac{1}{2}(cos(-\frac{3\pi}{40})+cos\frac{13\pi}{40})=\\ \\ =\frac{1}{2}(cos\frac{3\pi}{40}+cos\frac{13\pi}{40})=\frac{1}{2}cos\frac{3\pi}{40}+\frac{1}{2}cos\frac{13\pi}{40}

БОГ
10,984,878 заданий
13,471,016 решений
8,518,553 комментариев
4,909,216 пользователей